Studying Shear Performance of Flax Fiber-Reinforced Clay by Triaxial Test - Qiang Ma; Yicong Yang; Henglin Xiao; Wenwen Xing (Advances in Civil Engineering)
Laboratory triaxial tests were carried out to investigate the reinforcement mechanism, to study the characteristics of flax fiber-reinforced clay, and to discuss the effect on stress-strain relationship and shear strength parameters of flax fiber-reinforced clay in different flax fiber content and different confining pressure. Respectively, the ratio of fiber content to clay by weight is 0.2%, 0.4%, 0.6%, 0.8%, and 1.0%, and the confining pressure is 100 kPa, 200 kPa, and 300 kPa in triaxial test. The test results show that, the shear strength of flax fiber-reinforced clay is greater than that of pure clay. Compared with the pure clay, the shear strength of flax fiber-reinforced clay increased as the cohesion and friction increased; while the increase of the friction is relatively small, the increase of cohesion is large. The shear strength firstly increased and then reduced with the increase of flax fiber content. When the fiber content was 0.8%, the shear strength reached a peak value, and the shear strength reduced with the further increase of fiber content.